Degradation study of a reversible solid oxide cell (rSOC) short stack using distribution of relaxation times (DRT) analysis. (28th February 2022) - Nuggehalli Sampathkumar, Suhas; Aubin, Philippe; Couturier, Karine; Sun, Xiufu; Sudireddy, Bhaskar Reddy; Diethelm, Stefan; Pérez-Fortes, Mar; Van herle, Jan
Abstract: Reversible solid oxide cells (rSOC) can convert excess electricity to valuable fuels in electrolysis cell mode (SOEC) and reverse the reaction in fuel cell mode (SOFC). In this work, a five – cell rSOC short stack, integrating fuel electrode (Ni-YSZ) supported solid oxide cells (Ni-YSZ || YSZ | CGO || LSC-CGO) with an active area of 100 cm 2, is tested for cyclic durability. The fuel electrode gases of H2 /N2 :50/50 and H2 /H2 O:20/80 in SOFC and SOEC mode, respectively, are used during the 35 reversible operations. The voltage degradation of the rSOC is 1.64% kh −1 and 0.65% kh −1 in SOFC and SOEC mode, respectively, with fuel and steam utilisation of 52%. The post-cycle steady-state SOEC degradation of 0.74% kh −1 suggests improved lifetime during rSOC conditions. The distribution of relaxation times (DRT) analysis suggests charge transfer through the fuel electrode is responsible for the observed degradation. Graphical abstract: Image 1 Highlights: Degradation analysis of state-of-the-art reversible solid oxide cell. Application of EIS/DRT to isolate loss mechanisms responsible for degradation. Degradation rate comparison for rSOC cycles and post-cycling steady-state SOEC mode.